Acute Kidney Injury Increase Risk of Left Ventricular Remodeling: A Cohort of 1,573 Patients - Li, Qiang; Chen, Weihua; Shi, Shanshan; Huang, Haozhang; Lai, Wenguang; Liu, Liwei; Ying, Ming; Wang, Bo; Li, Huanqiang; Huang, Zhidong; Chen, Liling; Chen, Jiyan; et al. (Frontiers in Physiology, 2021)
Background: Acute kidney injury (AKI) is a common complication after coronary angiography (CAG) and associated with heart failure (HF). Left ventricular (LV) remodeling is a vital process in the progression of HF. However, few studies investigate the relationship between AKI and LV remodeling. Methods: We included consecutive patients undergoing CAG from January 2007 to December 2018 at Guangdong Provincial People's Hospital (NCT04407936). AKI was defined as an absolute increase in serum creatinine (Scr) of ≥0.3mg/dl or a ≥50% increase in Scr from baseline within the first 48 to 72 hours after the procedure. LV remodeling was defined as: 1) left ventricular ejection fraction (LVEF) decreased by ≥10 points from baseline, 2) a follow-up measurement of LVEF <40%. Univariate and multivariate logistical regressions were used to assess the association between AKI and LV remodeling. Results: Of the 1,573 patients (62.2±9.7 years, female 36.7%) included in the study, 231 (14.7%) had AKI. The prevalence of LV remodeling was higher in patients with AKI than in those without AKI (24.7% vs. 14.5%). After adjusting for confounding, multivariate logistic regression showed that AKI was associated with a significantly higher risk of LV remodeling (adjusted odds ratio [a OR] 1.89; 95% CI, 1.33–2.67; p<0.001). In addition, LV remodeling patients had higher all-cause mortality compared to non-LV remodeling patients (9.7% vs. 19.1%). Conclusions: Our data suggested that nearly a quarter of AKI patients suffered LV remodeling and AKI patients have a 2-fold risk of developing LV remodeling than non-AKI patients. Our findings notice that more active measures should be taken to prevent the patient with AKI from developing into LV remodeling.